Implementasi Corporate Social Responsibility pada Perusahaan PT. Perkebunan Nusantara III - SIMATUPANG, CHRISTIN DINAR SERE MUTIARA; BUDIASA, I WAYAN; WIDHIANTHINI, WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022, 2022)
Implementation of Corporate Social Responsibility of PT. Perkebunan Nusantara III.  Corporate Social Responsibility is the obligation of companies or the business world to make real contributions in achieving optimal business strategy by paying attention to social issues that exist in society and paying attention to the social conditions of the community where the company is located through the provision of CSR assistance. According to Law No.40 of 2007 on Limited Liability Companies, article 74 paragraph (1), companies are obliged to carry out social responsibility. This study aims to determine the implementation of CSR carried out by PTPN III Kebun Rantauprapat, as well as the company's strategy in addressing the regulations regarding social responsibility as stipulated in the law No.40 of 2007. Primary data were obtained from key informants and analyzed using descriptive qualitative methods. Research shows that PTPN III Kebun Rantauprapat has carried out its social responsibility obligations by providing assistance every year to stakeholders. CSR program implementation is implemented through socio-economic and environmental programs. The CSR program implemented by PTPN III has also complied with the regulations related to the implementation of social responsibility. The implementation of CSR is in accordance with the general guidelines as stipulated by the aforementioned the Law Regulation. PTPN III Kebun Rantauprapat should maintain and improve CSR programs for stakeholders, carry out programs that are beneficial to the community, develop productive CSR activities for stakeholders and increase activities that support a sustainable economy.